Consumer valuation of quality rice attributes in a developing economy: Evidence from a choice experiment in Vietnam - My, Nguyen H.D.; Van Loo, Ellen J.; Rutsaert, Pieter; Tuan, Tran Huu; Verbeke, Wim (Emerald Publishing Limited, 2018)
PurposeThe purpose of this paper is to investigate consumers’ willingness to pay for quality rice attributes in urban areas in the South of Vietnam, including organic and integrated pest management (IPM) as sustainable production methods, and claim about health benefits and fair farmer prices.Design/methodology/approachCross-sectional data were collected in 2015 using a survey including a choice experiment (CE) (n=500). Generalized mixed logit models were estimated.FindingsVietnamese consumers are willing to pay a premium of 82 percent for organic rice, and 45 percent for rice produced using IPM, compared to conventionally produced rice. They are also willing to pay a premium of 95 percent for rice claiming to be rich in vitamins and other nutrients, and 50 percent for rice that guarantees a fair price to rice farmers.Research limitations/implicationsA hypothetical CE was employed. Future research using revealed preference methods is suggested.Originality/valueThis study makes a significant contribution to the limited existing literature on consumers’ valuation of quality rice attributes in the context of developing countries such as Vietnam. The study shows that rice, that is, sustainably produced using organic or IPM methods provides a promising avenue for rice producers. This study highlights that there is an added value for rice with credence attributes in relation to sustainable production methods, health benefits, and fair farmer prices in a developing country.